Device-based 24-hour movement behaviours in adult phase III cardiac rehabilitation service-users during the COVID-19 pandemic: a mixed-methods prospective observational study - Melitta McNarry (Disability and Rehabilitation, 2024)
Purpose: To examine changes in device-based 24-hour movement behaviours (MB), and facilitatorsand barriers to physical activity (PA) and exercise, during remotely-delivered cardiac rehabilitation(RDCR).Materials and methods: This prospective observational study used wrist-worn GENEActivaccelerometers to assess MB of 10 service-users (63 ± 10 years) at the start, middle, and end ofthree-months of RDCR. Barriers and facilitators to PA and exercise were explored through self-reportdiaries and analysed using content analysis.Results: At start, service-users were sedentary for 12.6 ± 0.7 h day−1 and accumulated most PA at alight-intensity (133.52 ± 28.57 min day−1) – neither changed significantly during RDCR. Sleep efficiencysignificantly reduced from start (88.80 ± 4.2%) to the end (86.1 ± 4.76%) of CR, with values meetinghealth-based recommendations (≥85%). Barriers to RDCR exercise included exertional discomfort andcardiac symptoms, and reduced confidence when exercising alone. Setting meaningful PA goals,self-monitoring health targets, and having social support, facilitated PA and exercise during RDCR.Conclusions: Our RDCR programme failed to elicit significant changes in MB or sleep. To increase thelikelihood of successful RDCR, it is important to promote a variety of exercise and PA options, targetsedentary time, and apply theory to RDCR design, delivery, and support strategies.